2018
DOI: 10.5114/biolsport.2018.77824
|View full text |Cite
|
Sign up to set email alerts
|

Repeated-sprints exercise in daylight fasting: carbohydrate mouth rinsing does not affect sprint and reaction time performance

Abstract: To determine the effect of carbohydrate mouth rinsing (CHO-MR) on physical and cognitive performance during repeated-sprints (RS) after 3 days of intermittent fasting (abstaining from food and fluid 14 h per day). In a randomized and counter-balanced manner 15 active healthy males in a fasted state performed a RS-protocol [RSP; 2 sets (SET1 and SET2) of 5×5 s maximal sprints, with each sprint interspersed with 25 s rest and 3 min of recovery between SET1 and SET2] on an instrumented non-motorized treadmill wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
3
10
0
1
Order By: Relevance
“…Additionally, improvements in exercise performance after an oral carbohydrate rinse in comparison with a placebo rinse have been found with cycling [29][30][31][32][33], running [34][35][36][37] and resistance exercise [38]. In contrast, some studies have reported no significant improvements in exercise performance [39][40][41][42][43][44][45][46]. This lack of significant improvements may be due to the study design (i.e.…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, improvements in exercise performance after an oral carbohydrate rinse in comparison with a placebo rinse have been found with cycling [29][30][31][32][33], running [34][35][36][37] and resistance exercise [38]. In contrast, some studies have reported no significant improvements in exercise performance [39][40][41][42][43][44][45][46]. This lack of significant improvements may be due to the study design (i.e.…”
Section: Key Pointsmentioning
confidence: 99%
“…[2] NS Beelen et al [40] AVEBE (Veendam, The Netherlands) Black et al [70] L.D. Carlson Co., Kent, OH, USA Carter et al [28] NS Chambers et al [19] Roquette, France Cherif et al [41] SIS company, Nelson, UK Chong et al [42] Polycose, Ross Laboratory, Columbus OH Clarke et al [71] MyProtein, Manchester, UK Clarke et al [72] MyProtein, Manchester, UK Clarke et al [73] MyProtein, Cheshire, England, UK Cramer et al [74] NS de Oliveira et al [75] NS Decimoni et al [38] Body Action, Brazil Deighton et al [76] NS Dorling and Earnest [43] HighFive, Bardon, England Dunkin and Phillips [44] Bulk Powders TM, Colchester, UK Durkin et al [77] NS Fares and Kayser [31] NS Gam et al [45] Polycose, Ross Nutrition, Columbus, OH Green et al [78] Natural Foods Inc., Toledo, OH Jeffers et al [46] NS Jensen et al [79] NS Lane et al [32] NS Phillips et al [80] HighFive, Bardon, Leicestershire Přibyslavská et al [81] Letco Medical, Decatur, AL Rollo et al [82] MuscleTalk, Northhamptonshire, UK Rossato et al [83] Health Labs, Belo Horizonte, Brazil Simpson et al [84] Home Brew Supply LLC, TX, USA Sinclair et al [85] NS Whitham and McKinney [86] 97% polysaccharide, 2% disaccharide, 1% glucose; Roquette, Corby, UK performance outcomes, participant training status and exercise protocol.…”
Section: Performance Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the proportion of low-glycaemic-index foods in the suhoor meal (pre-fast) has been proposed, but this has little effect on subsequent aerobic performance 7 8. Buccal (mouth) rinses with carbohydrate-containing drinks may ameliorate some of the potential negative impacts of fasting but are of benefit only in endurance and not repeated sprint performance 9. Some athletes may choose to use this strategy, but it is important to note that there is a small risk of inadvertently swallowing fluid or for small quantities of carbohydrate or water to remain in the mouth after rinsing.…”
Section: Strategies To Help Athletes Perform In the Fasted Statementioning
confidence: 99%
“…Ternyata orang yang menjalani puasa 14 jam dan melakukan latihan seperti biasa tidak mengalami pengaruh pada waktu reaksi (Cherif et al, 2018), penelitian ini dilakukan berulang selama 3 hari berpuasa. Dilakukan pengujian waktu reaksi antara orang yang mengalami gangguan pendengaran dengan atlet, ditemukan bahwa atlet lebih pendek waktu yang diperlukan tetapi diantara sesama atlet dengan level kompetisi yang berbeda waktu reaksinya cenderung sama (Soto-Rey, Pérez-Tejero, Rojo-González, & Reina, 2014) Waktu reaksi antara atlet dan non atlet kenyataannya lebih bagus atlet (dengan sampel atlet bulu tangkis), tetapi faktor kemampuan untuk memproses kecepatan visual ini bukan saja dari kemampuan kemampuan visiomotor, dengan kata lain kemampuan perseptual visual bukan satu satunya indikator seseorang memiliki waktu reaksi yang cepat (Hülsdünker, Strüder, & Mierau, 2018).…”
unclassified